Gotong Royong Keuangan Sosial pada Etnis Mongondow : (Kajian Terhadap Tradisi Pogogutat Suku Mongondow ) - Mokoginta, Nurbaiti Siti Masita; Ilham, Ilham (Al-Buhuts, 2024)
The aim of this research is firstly, to find out how transactions and recording are carried out from the pogogutat tradition when viewed from the celebration organizers and celebration guests. As well as knowing whether or not there are regulations governing the pogogutat tradition from the local village government and the factors that become obstacles in its implementation. Second, it is hoped that this research can become a puzzle piece to complement existing literacy, and serve as reference material regarding social financial mutual cooperation in the form of local wisdom, especially the pogogutat tradition. The method used is a type of qualitative research with an ethnographic and legal sociology approach where researchers go into the field to carry out observations and in-depth interviews about transaction methods based on the object and time of exchange, recording, and regulations governing the implementation of this tradition. The research results showed that 1. The Pogogutat tradition in the Mongondow ethnic community in its implementation exchanges goods/food ingredients, services and money with exchange times that are not tied to time. To start/return the pogogutat there must be an invitation, then the tradition will not be carried out if the time for handing over and/or returning the pogogutat from both parties is both postponed. 2. Pogogutat recording has been around since the Mongondow ethnic community was able to read and write. 3. The pogogutat tradition in Bolaang Mongondow is regulated in Village Regulations regarding celebration parties. 4. In the pogogutat tradition there are also obstacles, namely that between people there are differences in character.